2023
DOI: 10.1126/sciadv.adf5500
|View full text |Cite
|
Sign up to set email alerts
|

Extreme enhancement of superconductivity in epitaxial aluminum near the monolayer limit

Abstract: BCS theory has been widely successful at describing elemental bulk superconductors. Yet, as the length scales of such superconductors approach the atomic limit, dimensionality as well as the environment of the superconductor can lead to drastically different and unpredictable superconducting behavior. Here, we report a threefold enhancement of the superconducting critical temperature and gap size in ultrathin epitaxial Al films on Si(111), when approaching the 2D limit, based on high-resolution scanning tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 74 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Finally, we discuss recent in situ scanning tunneling microscopy studies of ultraclean Al films grown on Si(111) [21]. In this work, a threefold enhanced T c (3.3 ± 0.1 K) was reported.…”
Section: Possible Mechanisms Leading To Enhanced T Cmentioning
confidence: 74%
See 1 more Smart Citation
“…Finally, we discuss recent in situ scanning tunneling microscopy studies of ultraclean Al films grown on Si(111) [21]. In this work, a threefold enhanced T c (3.3 ± 0.1 K) was reported.…”
Section: Possible Mechanisms Leading To Enhanced T Cmentioning
confidence: 74%
“…In our work, the presence of a thin overlaying AlO x layer when the Al film is exposed to air during ex situ processing does not hinder the enhanced superconductivity. Moreover, Si intermixing and Si doping cannot be the origins of the enhanced T c in the work of van Weerdenburg et al [21]. Hence, enhanced superconductivity is an intrinsic property of ultrathin Al films, provided the normal-state square resistance is much lower than the quantum resistance h/(4e 2 ).…”
Section: Possible Mechanisms Leading To Enhanced T Cmentioning
confidence: 95%
“…Very recently, van Weerdenburg [175] showed that in ultrathin Al films (8.5 ML film) a paramagnetic contribution from odd s-wave superconductivity gives rise to an enhanced magnetic penetration depth and an enhanced vortex size due to the Meservey-Tedrow-Fulde (MTF) effect [176]. The vortex size was measured in this paper via dI/dU-maps in STM/STS, and no magnetization data were reported.…”
Section: Odd S-wave Superconductivitymentioning
confidence: 75%
“…Future work on PME will consider very thin films of metallic superconductors, where significant progress has been made to fabricate uniform atomic monolayer films of Pb, Nb, Al, V, and MgB 2 [175,[178][179][180][181][182]. Giant PME may appear from non-monotonic vortex interactions as predicted in [174].…”
Section: Discussionmentioning
confidence: 99%